Penggunaan Teknologi dalam Pembelajaran: Peluang Dan Tantangan: Literature Review - Septiana, Ria Ayu; Subali, Bambang; Waluyo, Edi; Sumartiningsih, Sri; Yuwono, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Technology is advancing rapidly and has become an integral part of various aspects of life, including education. The use of technology in learning presents numerous opportunities but is not without its challenges. This study aims to examine the opportunities and challenges associated with the use of technology in education. The research employs a literature review method by gathering relevant sources related to the opportunities and challenges of integrating technology into learning. The findings reveal that the opportunities brought by technology in education include expanded learning accessibility, interactive learning experiences, personalized education, and the development of digital skills. However, the challenges include unequal access to technology, teachers' skills in training and mastering technological tools, the risk of distractions and disruptions caused by technology, and issues related to security and privacy. Therefore, the use of technology should be balanced and cautious, combining traditional approaches with modern ones to create a holistic and effective learning experience. With this balanced approach, technology serves as a tool to enrich education rather than as a replacement that diminishes the essence of true learning.